Synthesis, structures of mononuclear and dinuclear iron(II) complexes supported by non-symmetric guanidinate(amidinate) ligands. (15th February 2018) - Wang, Huan; Guo, Zeling; Tong, Hongbo; Zhou, Meisu
Graphical abstract: A family of iron(II) complexes containing guanidinato(amidinato) ligands were synthesized and characterized. Their structural features are discussed in detail. Abstract: A new family of Fe(II) compounds, 1 –3, have been prepared, which are derived from the non-symmetric lithium guanidinate Li(L1 ) [L1  = N(Ph)C(R)N(SiMe3 )] (R = 1-piperidino) or the lithium amidinates Li(L2 ) [L2  = N(Ph)C(Ph)N(SiMe3 )] or Li(L3 ) [L3  = N(2, 6- i Pr2 C6 H3 )C(Ph)N(SiMe3 )]. Treatment of Li(L1 ), Li(L2 ) or Li(L3 ) with anhydrous FeCl2 afforded [(L1 )4 Fe2 ] (1 ), [(L2 )4 Fe2 ] (2 ) or [{L3 }2 Fe] (3 ), respectively. The molecular structures of1 –3 were determined by an X-ray diffraction study.